Removal of Cd(II) from Aquatic System Using Oscillatoria sp. Biosorbent - Seyed Naser Azizi; Abasalt Hosseinzadeh Colagar; Seyede Maryam Hafeziyan (The Scientific World Journal)
Biosorption of Cd(II) ions from aqueous solutions by native and dried Oscillatoria sp. Cyanobacterium biomass was investigated in the batch mode. The Oscillatoria sp. was prepared from Molecular and Cell Laboratory of University of Mazandaran and grown in BG-11 medium. A comparison of Cd(II) adsorption properties of dried with native Oscillatoria sp. biomass was made, the dried one showed a higher biosorption capacity and faster kinetic. The influence of solution pH, contact time, biomass concentration, initial metal ion concentration, and presence of coions using dried Oscillatoria sp. biomass as well as pretreatment on the biosorption capacity of the biomass were studied. Various pretreatments of Oscillatoria sp. increased biosorption of Cd(II) at pH 7 in comparison with native biomass. However, heating at 100°C in a water bath showed significant improvement in Cd(II) biosorption capacity. The experimental biosorption data was well fitted to the Freundlich model compared to the Langmuir model, and the amount of Cd(II) removed from solution increased with increasing Cd(II) concentration. In addition, the dried biomass was investigated for Cd(II) removal from the simulated real sample containing about 14 mg/l Cd(II) at pH 7, under the same experimental condition.